Phosphoglucoisomerase Is an Important Regulatory Enzyme in Partitioning Carbon out of the Calvin-Benson Cycle - Preiser, Alyssa L.; Banerjee, Aparajita; Weise, Sean E.; Renna, Luciana; Brandizzi, Federica; Sharkey, Thomas D. (Frontiers in Plant Science, 2020)
Phosphoglucoisomerase (PGI) isomerizes fructose 6-phosphate (F6P) and glucose 6-phosphate (G6P) in starch and sucrose biosynthesis. Both plastidic and cytosolic isoforms are found in plant leaves. Using recombinant enzymes and isolated chloroplasts, we have characterized the plastidic and cytosolic isoforms of PGI. We have found that the plastidic PGI has at least a 3-fold higher Km for G6P compared to that for F6P and that erythrose 4-phosphate is a key regulator of PGI activity. Additionally the Km can be dynamically regulated in the dark compared to the light and increases by 200% in the dark. We also found that targeting cytosolic PGI into the plastid disrupts starch accumulation and degradation. Our results, in combination with the observation that plastidic PGI is not in equilibrium, support the that PGI is a key regulatory enzyme that may be manipulated to improve flow of carbon to desired targets of biotechnology.